Ask Question
13 October, 05:13

If f (x) = (x - 3) 2 + 4 and g (x) = x3 + 2, which statement is true?

(-2) = g (-3)

f (0) = g (-1)

f (8) = g (3)

f (2) = g (1)

+1
Answers (2)
  1. 13 October, 06:20
    0
    Replace x in each equation with the given choices and see which one is true:

    f (x) = (x - 3) 2 + 4

    g (x) = x3 + 2

    The answer is: f (8) = g (3)

    f (x) = (8-3) ^2 + 4 = 5^2 + 4 = 25 + 4 = 29

    g (x) = 3^3 + 2 = 27 + 2 = 29
  2. 13 October, 06:53
    0
    f (8) = g (3)

    Step-by-step explanation:

    f (x) = (x - 3) ^2 + 4 and g (x) = x^3 + 2

    We need to determine the values when we replace x

    f (-2) = (-2 - 3) ^2 + 4 = (-5) ^2 + 4 = 25+4 = 29

    f (0) = (0 - 3) ^2 + 4 = (-3) ^2 + 4 = 9+4 = 13

    f (2) = (2 - 3) ^2 + 4 = (-1) ^2 + 4 = 1+4 = 5

    f (8) = (8 - 3) ^2 + 4 = (5) ^2 + 4 = 25+4 = 29

    Now we find a g (x) value that matches one of these we are good

    g (-3) = (-3) ^3 + 2 = - 27 + 2 = - 25

    g (-1) = (-1) ^3 + 2 = - 1 + 2 = 1

    g (1) = (1) ^3 + 2 = 1 + 2 = 3

    g (3) = (3) ^3 + 2 = 27 + 2 = 29

    f (8) = 29 and g (3) = 29

    so f (8) = g (3)
Know the Answer?